The uneasy case of tortious interference with a contractual prohibition of assignment - Stoyanov, Dimitar (International Journal of Legal and Social Order, 2023)
Tortious interference with an existing contractual relation, induced by a third party, is regarded as a valid ground to impose extra-contractual liability upon the inducer. The following article aims to compare the different types of legal approach to this type of tort throughout a variety of national legislations. As it turns out, its field of application is quite broad and comprises both individuals and legal entities irrespective of their mercantile capacity. This leads to the issue about the possibility to apply the tort in case of a contractual prohibition of assignment. Despite the fact that all the necessary pre-requisites of this tort, set forth by the legislator or clarified by case law, can be established whenever there is a breach of the clause prohibiting assignment, national and supranational legislative acts seem reluctant to impose a tortious liability upon the assignee. The main reason for this circumstance is the influence, exerted by the respective provisions of the Uniform Commercial Code, that have subsequently been adopted by the United Nations Convention on Assignment in International Trade (2001). A glimpse upon various provisions of European legislations, as well as some relevant case law, reveal the lack of a uniform approach within the EU. The article puts to critical discussion the influence upon economic relations of an eventual introduction of extra-contractual liability imposed upon the assignee for inducing the breach of an anti-assignment clause.